Temsirolimus in the treatment of relapsed or refractory mantle cell lymphoma - Samad, Nousheen (Dove Medical Press, 2010)
Mantle cell lymphoma (MCL) is a rare and aggressive subtype of lymphoma associated with a poor prognosis. Chemotherapy is the mainstay of frontline treatment for patients with this disease. Despite high response rates to combination chemotherapy regimens, the majority of patients relapse within a few years of treatment. Therefore, finding efficacious treatments for relapsed or refractory disease has become a growing area of clinical research. The mammalian target of rapamycin (mTOR) is responsible for integrating cell signals from growth factors, hormones, and nutrients and communicating energy status. Scientific research on aberrant molecular pathways in cancer has revealed that several proteins along the mTOR pathway may be upregulated in this and other types of lymphoma. Temsirolimus is the first mTOR inhibitor that has shown clinical efficacy in treating MCL that has relapsed after frontline treatments.